Thermal radiative energy exchange between a closely-spaced linear chain of spheres and its environment. (April 2019) - Czapla, Braden; Narayanaswamy, Arvind
Highlights: Derived formulas for near-field radiative heat transfer in a chain of spheres. Calculated inter-sphere and sphere-environment radiative heat transfer. Developed model for experiment measuring radiative transfer between two spheres. Emphasized implications of sphere-environment interaction in near-field experiments. Abstract: In this work, we present expressions for radiative heat transfer between pairs of spheres in a linear chain and between individual spheres and their environment. The expressions are valid for coated spheres of arbitrary size, spacing, and isotropic optical properties. The spheres may be small and closely-spaced, which violates the assumptions foundational to classical radiative transfer. We validate our results against existing formulations of radiative heat transfer, namely the thermal discrete dipole and boundary element methods. Our results have important implications for the modeling and interpretation of near-field radiative heat transfer experiments between spherical bodies.